O desenvolvimento da linguagem oral e a sua relevância no processo de alfabetização : contribuições da psicologia histórico-cultural e da fonoaudiologia - Gomes, Tatiane Andressa de Almeida (2016)
The present study is a bibliographical and empirical research, whose goals were set up to study the development of oral language, from the perspective of Historical-Cultural Psychology, identifying its relevance in the literacy process and investigating the emphasis given by the teacher of early years of elementary school to the development of this language in the classroom. Initially this bibliographical research aimed to outline the development of the psyche, explaining about the superior psychological functions to then present the design related to the oral and written language. Then, it was clarified economic and social issues concerning the development of oral language, performing a counterpoint to the strands within the Speech-Language Therapy about the topic discussed. Subsequently, there was a historical review of this science in order to elucidate its action towards the education. Thereafter, it was found that, in view of the Historical-Cultural Theory, oral language is contemplated as essential to human development, since it is responsible for raising such a development to higher levels. In spite of fundamental to the constitution of man, the oral language, in this conception, differs from the written because this establishes through systematic teaching, while the constitution that is realized from social relations. Thus, there is the imminence of both oral language and the link between this and the written language that perspective. The empirical research was conducted in two public schools, located in the state of Paraná, which were conducted semi-structured interviews with seven teachers who work for 1st to 3rd grade of elementary school. It was carried out the analysis and the discussion of the collected material, based on the perspective of the Historical-Cultural Theory. The results showed that with regard to understanding the development of oral language, some participants addressed succinctly relevant questions about this axis though, there was no further theoretical study in their majority, the data showed a reductionist and impervious design. Concerning the teaching mediation and the development of oral language, participants reported understand the importance of mediation and carried out activities that contribute to this; however, these reports contradicted this practice due to the great demand referred for evaluation and Speech-Language Therapy trials without the actual need. As for the factors that favor the development of oral language and literacy, interviewees attributed the success of this development to the maturation of the student, to the family, simplifying this process, demonstrating a reductionist and flawed concept that discredit the profession in itself. Worth noting that only one of the participants stressed the importance of teacher planning and social issues among these factors. Reflecting on these notes, there was the urgent need for insertion of Linguistics discipline in the curriculum of Pedagogy, the need to conduct systematic training for teachers to not only pass the contents on the oral language development and writing, as well as encourage them to understand that their role effectively in the process of oral language development, and especially the written language is essential.